(untitled) (Innovaciones Educativas, 2024)
This text analyzes the phenomenon of teacher influencers, highlighting their definition, the challenges they face and the opportunities they offer both in education and in the media. Influencer teachers are professionals who, in addition to their work in the classroom, use digital platforms and social networks to share educational content, interact with their communities and generate impact beyond the traditional school environment. Among the challenges they face are managing public exposure, reconciling their role as teachers and content creators, and adapting to the demands of the digital age. However, this phenomenon also offers new perspectives to transform education, favoring pedagogical innovation and access to educational resources. Through these platforms, they contribute to the democratization of knowledge and the strengthening of a more connected and collaborative educational community.